ANALISIS NILAI EKONOMI USAHA TAMBAK NILA, BANDENG DAN UDANG WINDU TERHADAP KESEJAHTERAAN PETAMBAK DI KAWASAN MANGROVE KELURAHAN NELAYAN INDAH, MEDAN LABUHAN - Meia Ester Sela Ginting; Yunasfi Djayus; Febrina Arli (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Village Nelayan Indah is community conduct farming in mangrove areas that affect the welfare of farmers. The focus of research are to see mangrove population, economic value analysis of the level of tilapia (Oreochromis niloticus), milkfish (Chanos chanos), and tiger shrimp (Penaeus monodon) with welfare of farming. The method used purposive sampling (intentionally). Based on the research object are the society with the primary livelihood as farmers from one of these commodities in the mangrove areas of Village Nelayan Indah in April until May 2015. Mangrove populations were analyzed by the method of line transect 2 census pioneered. Economic value analysis are based on a detailed questionnaire to see income, benefit cost ratio (BCR) and the payback period (PP) and the level of welfare in quantitative and descriptive. The results of the study indicates that are mangrove population in lines 1, 2 are Rhizophora apiculata mangrove populations and the lowest result in the lines 1, 2 are Avicennia alba. Analysis of the economic value of the tilapia ponds income Rp.261.149.000 hectares per year with a value of BCR 7,61 and 0,11 years of PP grades. Milkfish revenue of Rp.192.215.617 hectares per year with a value of 11,04 and PP 0,17 BCR Year. Shrimp farm income of Rp.125.183.133 hectares per year as well as the BCR 7 with PP of 0,39 years. The level of welfare of tilapia farmers more prosperous than the two other commoditiesKeywords: fishpond economic, welfare, mangrove